2009
DOI: 10.1007/s00439-009-0638-5
|View full text |Cite
|
Sign up to set email alerts
|

The genomic basis of cerebral palsy: a HuGE systematic literature review

Abstract: Cerebral palsy has been associated with a number of candidate genes. To date, no systematic review has been conducted to synthesise genetic polymorphism associations with cerebral palsy. We apply the HuGE NET guidelines to search PubMed and EMBASE databases for publications investigating single nucleotide polymorphisms (SNPs) and cerebral palsy outcome. 22 papers were identified and are discussed in this review. Candidate genes were grouped as (1) thrombophilic, (2) cytokine, (3) apolipoprotein E or (4) other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 82 publications
(93 reference statements)
0
40
0
2
Order By: Relevance
“…8,9 SNP association studies have been reported but have provided inconclusive results because of small sample sizes. 10 A genetic linkage study mapped an autosomal recessive type of spastic CP to a locus on chromosome 2p24-25 11 and subsequently, a missense variant was found in the GAD1 gene, which segregated with the CP phenotype (LOD score 5.75). 12 However, the functional effect of this variant was not assessed and no GAD1 variants have since been found in other individuals with CP.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 SNP association studies have been reported but have provided inconclusive results because of small sample sizes. 10 A genetic linkage study mapped an autosomal recessive type of spastic CP to a locus on chromosome 2p24-25 11 and subsequently, a missense variant was found in the GAD1 gene, which segregated with the CP phenotype (LOD score 5.75). 12 However, the functional effect of this variant was not assessed and no GAD1 variants have since been found in other individuals with CP.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic influences affecting CP have been the subject of much attention in recent years. [10][11][12]20,21 Several genes have been identified as risk factors, and have been categorized as thrombophilic, cytokine, apolipoprotein E and a group related to cardiovascular physiology and the functioning of the immune system. 21 Among the candidate genes, several SNPs of the MTHFR genes have been investigated either in normal populations or CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Methods by Vojta and Bobath concept belong to universally known approached for rehabilitation. Method by Semenova has been also recognized in Europe [19] (Russia) -which consisted in use of anti-gravitation suits as well as the method after prof. Kozyavkin [20] (Ukraine) -a system of intensive neurophysiology rehabilitation.…”
Section: Introductionmentioning
confidence: 99%